1989
DOI: 10.1007/bf00224734
|View full text |Cite
|
Sign up to set email alerts
|

Intramural distribution of immunoreactive vasoactive intestinal polypeptide (VIP), substance P, somatostatin and mammalian bombesin in the oesophago-gastro-pyloric region of the human gut

Abstract: The intramural distribution of vasoactive intestinal polypeptide (VIP), substance P, somatostatin and mammalian bombesin was studied in the oesophago-gastro-pyloric region of the human gut. At each of 21 sampling sites encompassing this entire area, the gut wall was separated into mucosa, submucosa and muscularis externa, and extracted for radioimmunoassay. VIP levels in the mucosa were very high in the proximal oesophagus (1231 +/- 174 pmol/g, mean +/- SEM) and showed varied, but generally decreasing concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Wattchow et al suggested that these subepithelial fibres may be sensory or sensorimotor28 with cell bodies in the submucosal or myenteric plexus. In the oesophagus of man submucosal ganglia are sparse,32 in contrast with their increased number in the more distal gut.…”
Section: Discussionmentioning
confidence: 97%
“…Wattchow et al suggested that these subepithelial fibres may be sensory or sensorimotor28 with cell bodies in the submucosal or myenteric plexus. In the oesophagus of man submucosal ganglia are sparse,32 in contrast with their increased number in the more distal gut.…”
Section: Discussionmentioning
confidence: 97%
“…The peptide appears to be located mainly in endocrine cells in the mucosa, but it does not seem to occur in every region (Ferri et al , 1989Keast et al 1984). Somatostatin-immunoreactive nerves were found throughout the gut except in the gastric body.…”
Section: Discussionmentioning
confidence: 93%
“…NKB is not present in pig stomach [13], and has not been found in gut tissue of any species, whereas small amounts of the precursor of NKA, neuropeptide K, are present in the porcine antrum [13]. In humans extractable SP immunoreactivity was found throughout the stomach, with increasing concentrations towards the distal part [12]. The aboral rise in SP concentration was seen in both the mucosa, the submucosa and the muscle layer.…”
Section: Localization In the Stomachmentioning
confidence: 87%